Choice suitable stainless steel as a construction material for zinc hydrometallurgy - Dušan Stanojević; Milana Tomić (Zaštita Materijala)
Beside vast usage in everyday life, stainless steels present important construction materials in many industrial fields (chemical, food producing and pharmaceutical industries, energetics, transport, mining, metallurgy, etc.). In zinc hydrometallurgy, based on sulphur-acid solutions of complex composition which show high corrosion aggressiveness, it is very difficult to find suitable construction materials. For that purpose, different materials are used, among them are some stainless steels, but all achieved results, from these or those reasons, are mostly unsatisfactory. This paper examines the usage of four contemporary stainless steels (Uranus B6, Sanikro 25, 316L and 4573) in original solutions from electrolytic zinc production, at operating temperature of 95°C, as well as their corrosion behaviour. Based on the examination results, it is established that these materials would be of limited usage in actual conditions, in operating solutions from production process due to incomplete passiveness and possible pitting corrosion.